A study to assess the knowledge and practice regarding sanitation and hygiene among women living in selected areas of Dhaka city - Hossain, Sophia; Kouser, M.; Jannat, Noore; Malek, Abdul; Chowdhury, Imtiaj Hossain (International Journal Of Community Medicine And Public Health, 2024)
Background: Access to improved sanitation and hygiene is one of the prime concerns around the globe. This study aimed at assessing knowledge and practice regarding sanitation and hygiene among women living in selected areas of Dhaka city. Methods: A community-based cross-sectional study was conducted in the urban slums of Vellore using the systematic random sampling method. Data was analyzed using frequency and WASH scoring. Further bi-variate and multivariate analyses was done using chi-square test and logistic regression. A total number of 140 households were surveyed using a semi-structured, pilot-tested questionnaire. Results: The 230 participants, with a mean age of 43.2 years, who were mostly from nuclear families (72.6%) and had monthly family incomes of at least 20,000 BDT, were included in the study. The 37% of respondents had hygienic sanitation facilities, while 42% of respondents had access to Kacha latrines. 69% of the participants used sandals while defecating, and 64% washed their hands with water and soap or ash. A significant association between WASH practices and household members with less than five members and upper middle SES group was found by multivariate logistic regression analysis, with a significance level of less than 0.01. Conclusions: Since good hygiene will stop the spread of infectious diseases, knowledge and practice of proper personal hygiene and sanitation are essential in day-to-day living. Comprehensive knowledge, more awareness programs, and subsidy policies should be implemented in order to improve sanitation and reduce the burden of transmissible diseases while taking into account regional variations in hygiene practice.